Flexural behavior of ultra-high performance hybrid fiber reinforced concrete at the ambient and elevated temperature - Li, Ye (2022)
This study investigates the flexural performance of a hybrid polyethylene-steel fiber-reinforced ultra-high performance concrete. Effects of different levels of fibers hybridization, aggregate size, water-to-binder ratio and exposed temperature on the load-deflection curves, toughness, and toughness index of UHPFRC are examined. Results indicate that a hybrid combination of polyethylene (PE) and steel fibers effectively enhanced limit of proportionality, modulus of rupture, toughness, and toughness index of UHPFRC. UHPFRC with 0.5 vol% PE and 2.0 vol% steel fibers in the current study shows the best flexural performance. Higher water-to-binder ratio and smaller aggregate reduce flexural performance of UHPFRC. Compared to polypropylene (PP) fibers, PE fibers have very limited effects on spalling prevention. Flexural performance of PE-steel hybrid UHPFRC is significantly reduced after exposure to elevated temperature.